Ecocriticism - Garrard, Greg (Abingdon, Oxon ; New York : Routledge, 2012)
Inspired by a range of ecological movements, ecocriticism explores the ways in which we imagine and portray the relationship between humans and the environment in all areas of cultural production, from Wordsworth and Thoreau to Disney and BBC nature documentaries. Greg Garrard's animated and accessible volume traces the development of the movement and explores the concepts which have most occupied ecocritics, including: * pollution * wilderness * apocalypse * dwelling * animals * earth. Featuring an invaluable glossary of terms and suggestions
1. Beginnings: Pollution 2. Positions 3. Pastoral 4. Wilderness 5. Apocalypse 6. Dwelling 7. Animals 8. Futures: The Earth
Includes bibliographical references and index.
ENH
Trim Education
Keywords: English literature -- History and criticism -- Theory, etc; Nature in literature; American literature -- History and criticism -- Theory, etc; Conservation of natural resources in literature; English literature; Environmental protection in literature; Philosophy of nature in literature; Forests in literature; Wilderness areas in literature; Outdoor life in literature; Ecology in literature; Landscapes in literature; Ecocriticism; Criticism -- Great Britain; Criticism -- United States